Analisis Efisiensi Alokatif Faktor Produksi Usahatani Ubi Kayu di Desa Makkawaru Kecamatan Mattirobulu Kabupaten Pinrang - Aliah, Amaliah Fitrah; Mudatsir, Rasdiana; Asriadi, Andi Amran (MuJAgri: Musamus Journal of Agribusiness, 2024)
Agriculture is critical to Indonesia's development and poverty alleviation efforts. In Pinrang District, South Sulawesi, cassava cultivation is a major driver of the local economy, especially in Mattiro Bulu Sub-district. The study aims to analyze how efficient the allocation of the use of input factors in cassava production is. The study used a random sampling method where samples were taken randomly, involving 32 cassava farmers from a population of 215 people. Findings in the Cobb Douglass regression testing research of the independent variables that have a real effect on cassava production are X1, X2, X3 and X4 have no real effect. Meanwhile, the allocative efficiency that X1, X2, X3 and X4 are at the level of inefficient allocation. This condition occurs because the efficiency value of production factor inputs has not reached 1. This needs to be adjusted by reducing the number of inputs used in the cassava production process.